X‐ray computed tomography quantification of damage in concrete under compression considering irreversible mode‐II microcracks. Issue 12 (12th April 2017) - Yu, Z.W.; Tan, S.; Shan, Z.; Tian, X.Q.
Abstract: A method for X‐ray computed tomography quantification of damage in concrete under compression considering irreversible mode‐II microcracks is developed. To understand damage behaviour in concrete, a micromechanical analysis of damage under biaxial compression is conducted focusing on random micro‐defects in micro‐cells isolated from the representative volume element. Furthermore, for stress–strain response prediction, a quantification is developed concerning the behaviours of the dominant macrocracks in multiaxial compression. Specifically, two crack types are taken into account: mode‐I cracks and irreversible deformation cracks (including mode‐II microcracks). Furthermore, mode‐I cracks generate compression‐induced tensile load (transverse) area reduction and further stiffness degradation, whereas the latter contribute to the development of irreversible strains. Additionally, by investigating the development of gradually converging dominant cracks, the procedure for quantifying damage is competently executed. In addition, distinguished from other approaches, the quantified damage can be applied directly to constitutive models to produce stress–strain response highly agrees with experimental results.